KAJIAN BUDAYA ETNIS DALAM MENGEMBANGKAN KEPRIBADIAN SOSIAL MASYARAKAT DI KECAMATAN JAGOI BABANG KABUPATEN BENGKAYANG PERBATASAN INDONESIA-MALAYSIA - Aminuyati, Aminuyati; Marpaung, Evlin; Saputra, Jepri; Nikita, Nikita; Yuda, Yuda (Universitas Tanjungpura, 2022)
The results of the long-term research are that the implementation of justice, equity and development for the community at the grassroots level in Indonesia through development policies is a functional organizational unit of the relevant Service Office which is given the responsibility to increase the degree of ethnic cultural ability in developing social personality specifically in the border area with Sarawak, East Malaysia, which in terms of culture, infrastructure, facilities and human resources are better. Impact for the long term, the results of this study can be used as a reference because the stakeholders provide the best guarantee to pay attention to the people who are supported by ethnic culture.